The 2009 world forecasts of glassware for laboratory, hygienic, or pharmaceutical use export supplies [electronic resource] - Parker, Philip M. , 1960- (Icon Group, 2009)
This report was created for strategic planners, international marketing executives and export managers whose primary concern is the world market for glassware for laboratory, hygienic, or pharmaceutical use. With the globalization of this market, managers can no longer be contented with a local view. Nor can managers be contented with out-of-date statistics that appear several years after the fact. I have developed a methodology, based on macroeconomic and trade models, to estimate the market for glassware for laboratory, hygienic, or pharmaceutical use for those firms serving the world via exports and foreign direct investment. It does so for the current year based on a variety of key historical indicators and econometric models.